Evaluation of some prescribed and over-the-counter drugs induced hemato-biochemical changes in mice - Amin, Mohammad Rohul; Khanam, Shukhi; Mazumder, Lalin; Rahman, ABM Zunayeed; Anower, AKM Mostafa; Mollah, Mohammad Lalmoddin (Asian Journal of Medical and Biological Research, 2020)
The present study was performed in the Department of Physiology and Pharmacology, Faculty of Animal science and Veterinary Medicine, PSTU, Bangladesh. Data were collected using a semi-structured questionnaire from 125 people in Babugonj upazilla, Barishal for using drugs without prescription or at prescription. The experiment was conducted to evaluate the effects of prescribed and over-the-counter drugs on hematological (TEC, Hb and DLC) and biochemical (blood glucose) parameters in mice during the period March to April, 2019. 140 male mice were randomly divided into seven groups (A, B, C, D, E, F and G), each consisting of 20 mice. Group A was kept as control. Paracetamol, diclofenac, pantoprazole, ranitidine, diazepam and clonazepam were administered orally to mice of group B, C, D, E, F and G, respectively for 28 days. Paracetamol and ranitidine were used by 100% people followed by peantoprazole (80.80%), diclofenac-60%, diazepam-42.40% and clonazepam-24%, respectively without prescription. Paracetamol were used by 100% people followed by peantoprazole (84%), ranitidine-76%, diclofenac-66.40%, clonazepam-53.60% and diazepam 32.80%, respectively at prescription. Paracetamol and diazepam decreased significantly (p<0.05) total erythrocyte count (TEC) at 28th day. Paracetamol, diclofenac and diazepam decreased significantly (p<0.01 and p<0.05) hemoglobin content (Hb) at 28th day. The Differential leukocyte count (DLC) was not significantly changed at 28th day in mice. Paracetamol, diclofenac, pantoprazole, ranitidine, diazepam and clonazepam increased significantly (p<0.01 and p<0.05) blood glucose level in mice. It may be concluded that paracetamol is one of the most frequently used and self prescribing drugs in Bangladesh. Asian J. Med. Biol. Res. June 2019, 5(4): 297-302